A framework for identifying paper parks - Jessica L. Stewart; Naomi Kingston; Natasha Ali; Heather C. Bingham; Zoe G. Davies; Nigel Dudley; Charlie J. Gardner; Jonas Geldmann; Diego Juffe-Bignoli; Thomas Pienkowski; Rachel E. Sykes; Neil D. Burgess; et al. (Biological Conservation, 2026)

Assessing South Africa’s marine protected area quality and progress towards conservation goals: An application of The MPA Guide framework - Laurel C. Field; Kendyl Wright; Jenna Sullivan-Stack; Jean M. Harris; Stephen P. Kirkman; Peter J. Fielding; Ané Oosthuizen; Siyabonga Dlulisa; Anastasiya Laznya; Emanuel J. Gonçalves; Kirsten Grorud-Colvert (Marine Policy, 2025)

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

When are bacteria really gazelles? Comparing patchy ecologies with dimensionless numbers - Samuel S. Urmy; Alli N. Cramer; Tanya L. Rogers; Jenna Sullivan‐Stack; Marian Schmidt; Simon D. Stewart; Celia C. Symons (Ecology Letters, 2022)
From micro to planetary scales, spatial heterogeneity—patchiness—is ubiquitous in ecosystems, defining the environments in which organisms move and interact. However, most large‐scale models still use spatially averaged ‘mean fields’ to represent natural populations, while fine‐scale spatially explicit models are mostly restricted to particular organisms or systems. In a conceptual paper, Grünbaum (2012, Interface Focus 2: 150–155) introduced a heuristic, based on three dimensionless ratios quantifying movement, reproduction and resource consumption, to characterise patchy ecological interactions and identify when mean‐field assumptions are justifiable. We calculated these dimensionless numbers for 33 interactions between consumers and their resource patches in terrestrial, aquatic and aerial environments. Consumers ranged in size from bacteria to whales, and patches lasted from minutes to millennia, with separation scales from mm to hundreds of km. No interactions could be accurately represented by naive mean‐field models, though 19 (58%) could be partially simplified by averaging out movement, reproductive or consumption dynamics. Clustering interactions by their non‐dimensional ratios revealed several unexpected dynamic similarities. For example, bacterial Pseudoalteromonas exploit nutrient plumes similarly to Mongolian gazelles grazing on ephemeral steppe vegetation. We argue that dimensional analysis is valuable for characterising ecological patchiness and can link widely different systems into a single quantitative framework.